ChemInform Abstract: Catalytic Lewis Acid Phosphorylation with Pyrophosphates. Issue 10 (7th March 2013) - Fenton, Owen S.; Allen, Emily E.; Pedretty, Kyle P.; Till, Sean D.; Todaro, Joseph E.; Sculimbrene, Bianca R.
Abstract This is a useful method for phosphorylation of primary and secondary alcohols.